2015
DOI: 10.1016/j.ajog.2014.11.014
|View full text |Cite|
|
Sign up to set email alerts
|

Two practice models in one labor and delivery unit: association with cesarean delivery rates

Abstract: Objective To examine the association between labor and delivery practice model and cesarean delivery rates at a community hospital. Methods This was a retrospective cohort study of 9,381 singleton live births at one community hospital, where women were provided labor and delivery care under one of two distinct practice models: a traditional “private” practice model and a midwife-physician “laborist” practice model. Cesarean rates were compared by practice model, adjusting for potential sociodemographic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 29 publications
6
53
1
Order By: Relevance
“…We previously reported that primary cesarean delivery rates at a single institution in Northern California were lower among publically insured women who delivered under a laborist model that includes 24-hour in-hospital midwifery coverage than among privately insured patients who delivered under a traditional private practice model (16). In this report we present results of an analysis of the expansion of this laborist-midwifery model to privately insured patients.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that primary cesarean delivery rates at a single institution in Northern California were lower among publically insured women who delivered under a laborist model that includes 24-hour in-hospital midwifery coverage than among privately insured patients who delivered under a traditional private practice model (16). In this report we present results of an analysis of the expansion of this laborist-midwifery model to privately insured patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest these investments are warranted, because some research shows that obstetric and obstetric and gynecologic hospital medicine practices may reduce the risk of cesarean delivery, increase rates of vaginal births after cesarean delivery, and, as part of a comprehensive safety program, reduce adverse events and malpractice claims and payments. [12][13][14][15][16] The use of standardized definitions will clarify interpretation of these investigations. The Society of Obstetric and Gynecologic Hospitalists supports all efforts to improve the quality and safety of inpatient women's health care.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Comprehensive obstetric safety initiatives, which have included implementation of OB/GYN hospitalist programs at Yale University and New York Presbyterian-Weill Cornell Medical Center achieved substantial reductions in adverse outcomes, malpractice claims, and payouts on malpractice cases. 8,9 Additional components of these initiatives included the use of standardized protocols, obstetric safety nurses, anonymous event reporting, team training and electronic fetal heart rate monitoring certification, and cultural change led by the OB/GYN hospitalist.…”
Section: Do Obstetrics/gynecology Hospitalists Improve Care?mentioning
confidence: 99%